Successful Management of Peripartum Cardiomyopathy (Anwer Khan Modern Medical College Journal, 2017)
Peripartum cardiomyopathy is a rare form of cardiac disorder of unknown origin associated with a high risk of mortality (50%). Echocardiogram confirms the diagnosis by typically reveals a left ventricular dialatation and a decreased ejection fraction (45%). Up to date, the treatment remains symptomatic. The prognosis is variable, ranging from complete recovery to worsening heart failure. Future pregnancy often discourge because of high mortality rate and risk of recurrence. Prognosis is related to recovery of ventricular fuction. Among many cases we report 3 more complicated cases of peripartum cardiomyopathy that managed successfully in our hospital.Anwer Khan Modern Medical College Journal Vol. 8, No. 1: Jan 2017, P 67-70